The relationship between innovation, knowledge, and performance in family and non-family firms: An analysis of SMEs - David P. Price; Michael Stoica; Robert J. Boncella (Journal of Innovation and Entrepreneurship, 2013)
This study seeks to examine the relationship between innovation and knowledge in family versus non-family businesses with regard to performance. Data from 430 small and medium-sized enterprises were analyzed through hierarchical regression analysis, and innovation was found to be a significant factor in both family and non-family samples. However, knowledge in family firms was also found to be significant with innovation. Implications for theory and practice are discussed that may provide possible competitive advantage for small family firms.
Keywords: 650; family firms; innovation; knowledge resources; SMEs